Study protocol: Mother and Infant Nutritional Assessment (MINA) cohort study in Qatar and Lebanon. Issue 1 (December 2016) - Naja, Farah; Nasreddine, Lara; Al Thani, Al; Yunis, Khaled; Clinton, Michael; Nassar, Anwar; Farhat Jarrar, Sara; Moghames, Patricia; Ghazeeri, Ghina; Rahman, Sajjad; Al-Chetachi, Walaa; Sadoun, Eman; et al.
Abstract Background The Middle East and North Africa region harbors significant proportions of stunting and wasting coupled with surging rates of non-communicable diseases (NCDs). Recent evidence identified nutrition during the first 1000 days of life as a common denominator not only for optimal growth but also for curbing the risk of NCDs later in life. The main objective of this manuscript is to describe the protocol of the first cohort in the region to investigate the association of nutrition imbalances early in life with birth outcomes, growth patterns, as well as early determinants of non-communicable diseases. More specifically the cohort aims to1) examine the effects of maternal and early child nutrition and lifestyle characteristics on birth outcomes and growth patterns and 2) develop evidence-based nutrition and lifestyle guidelines for pregnant women and young children. Methods/design A multidisciplinary team of researchers was established from governmental and private academic and health sectors in Lebanon and Qatar to launch the Mother and Infant Nutritional Assessment 3-year cohort study. Pregnant women (n  = 250 from Beirut, n  = 250 from Doha) in their first trimester are recruited from healthcare centers in Beirut, Lebanon and Doha, Qatar. Participants are interviewed three times during pregnancy (once every trimester) and seven times at and after delivery (when the child is 4, 6, 9, 12, 18, and 24 months old). Delivery and birth data is obtained from hospital records. Data collection includes maternal socio-demographic and lifestyle characteristics, dietary intake, anthropometric measurements, and household food security data. For biochemical assessment of various indicators of nutritional status, a blood sample is obtained from women during their first trimester. Breastfeeding and complementary feeding practices, dietary intake, as well as anthropometric measurements of children are also examined. The Delphi technique will be used for the development of the nutrition and lifestyle guidelines. Discussion The Mother and Infant Nutritional Assessment study protocol provides a model for collaborations between countries of different socio-economic levels within the same region to improve research efficiency in the field of early nutrition thus potentially leading to healthier pregnancies, mothers, infants, and children.